DESA BENGKALA DAN PEMENUHAN HAK POLITIK DALAM PEMILU (Studi Kasus Kaum Disabilitas Desa Bengkala Dalam Pemilukada 2017) - Andika, Riko Firman; Noak, Piers Andreas; Bandiyah, Bandiyah (Jurnal Nawala Politika, 2018)
ABSTRACT Persons with disabilities (PwDs) in Indonesia are still discriminated, especially on election day. Persons with disabilities in elections have not been fully considered. However, Bengkala Village, Buleleng, Bali Province is able to improve and fulfill the political rights for PwDs. Bengkala Village as a best practice for the needs of PwDs and success as an inclusive Election organizer. This research uses descriptive qualitative method with purposive sampling technique. In seeing the success of Bengkala Village to fulfill the political rights of disability is by using three theories namely: participation theory, rational choice theory, and dramaturgy theory. The three theories dissect disability community relationships with the fulfillment of political rights in elections in Bengkala Village . The purpose of this study is to find out how Bengkala village can fulfill the political rights of the disability. The findings of this research are, firstly, Bengkala Village meets as inclusive village for people with disability, this is inseparable from a Putu Kanta volunteer who supports the existence of people persons with disabilities. Secondly, although there are problems from the KPU, but people with disabilities can still run an inclusive 2017 Election. Third, the success of Pemilukada in Bengkala village was established in livelihood.   Keywords: BengkalaVillage, Disability, Election, Fulfillment of Political Rights.